EMC1 Is Required for the Sarcoplasmic Reticulum and Mitochondrial Functions in the Drosophila Muscle - Couto-Lima, Carlos Antonio [UNESP] (2024)
EMC1 is part of the endoplasmic reticulum (ER) membrane protein complex, whose functions include the insertion of transmembrane proteins into the ER membrane, ER–mitochondria contact, and lipid exchange. Here, we show that the Drosophila melanogaster EMC1 gene is expressed in the somatic musculature and the protein localizes to the sarcoplasmic reticulum (SR) network. Muscle-specific EMC1 RNAi led to severe motility defects and partial late pupae/early adulthood lethality, phenotypes that are rescued by co-expression with an EMC1 transgene. Motility impairment in EMC1-depleted flies was associated with aberrations in muscle morphology in embryos, larvae, and adults, including tortuous and misaligned fibers with reduced size and weakness. They were also associated with an altered SR network, cytosolic calcium overload, and mitochondrial dysfunction and dysmorphology that impaired membrane potential and oxidative phosphorylation capacity. Genes coding for ER stress sensors, mitochondrial biogenesis/dynamics, and other EMC components showed altered expression and were mostly rescued by the EMC1 transgene expression. In conclusion, EMC1 is required for the SR network’s mitochondrial integrity and influences underlying programs involved in the regulation of muscle mass and shape. We believe our data can contribute to the biology of human diseases caused by EMC1 mutations.